Pengolahan Limbah Biji Rambutan Menjadi Emping Tolang Buluan di Desa Karang Bayan Kecamatan Lingsar - Nila Sari; Melyana Melyana; Umul Kalsum; Agus Ramdani (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2023)
So far, people consider rambutan seeds as unused waste, even though rambutan seeds have many health benefits. The purpose of the activities carried out by UNRAM Integrated KKN students is so that people can utilize rambutan seeds into products that have sales value. This activity was carried out in Karang Bayan Village, Lingsar District, West Nusa Tenggara. The approach used in this activity is Learning by Doing. UNRAM's integrated KKN student team learned by practicing directly how to process rambutan seeds with the tools and materials that had been prepared. This approach is expected to be more effective in achieving the output targets in KKN activities in Karang Bayan Village. The results of the implementation of the Integrated Community Service Program (KKN) activities are able to provide information and innovation about processing rambutan seed waste so that the community is able to process rambutan seed waste into a creative business venture, which is able to show creativity in turning unused waste into a valuable product. In addition, this activity can also be an option to reduce waste, especially rambutan seeds.